Inomhusklimat i skolor- En jämförelse mellan upplevt och uppmätt inomhusklimat - Larsson, Hanna; Arén, Gustaf (My University, 2013)
Students’ performance in school is dependent on the indoor climate. This report studies four schools regarding air quality and thermal environment. A survey was made at the schools as well as measurements of carbon dioxide, dampness, thermal climate and, as an indicator for the furniture’s capability to collect dust, shelf factor and fleece factor. The results from each school were compared. Results show that at three out of four schools where levels of carbon dioxide, that by the Swedish recommendations are considered as satisfactorily, were measured, had, according to the survey, the worst air quality. At the same schools, cleaning and sanitation were considered unsatisfactorily. The school that had levels of carbon dioxide above what is considered as satisfactorily was the school that, according to the survey, had the best air quality. The magnitude of this study is too small to make any definite conclusions. The result, however, gives an indication on which parameters can be considered in further studies.
Keywords: Samhällsbyggnadsteknik; Energi; Building Futures; Civil Engineering; Energy; Building Futures